Insights into the pathogenicity of rare missense GCK variants from the identification and functional characterization of compound heterozygous and double mutations inherited in cis. - Beer, N; Osbak, K; van de Bunt, M; Tribble, N; Steele, A; Wensley, K; Edghill, E; Colcough, K; Barrett, A; Valentínová, L; Rundle, J; Raimondo, A; et al. (2012)
OBJECTIVE: To demonstrate the importance of using a combined genetic and functional approach to correctly interpret a genetic test for monogenic diabetes. RESEARCH DESIGN AND METHODS: We identified three probands with a phenotype consistent with maturity-onset diabetes of the young (MODY) subtype GCK-MODY, in whom two potential pathogenic mutations were identified: [R43H/G68D], [E248 K/I225M], or [G261R/D217N]. Allele-specific PCR and cosegregation were used to determine phase. Single and double mutations were kinetically characterized. RESULTS: The mutations occurred in cis (double mutants) in two probands and in trans in one proband. Functional studies of all double mutants revealed inactivating kinetics. The previously reported GCK-MODY mutations R43H and G68D were inherited from an affected father and unaffected mother, respectively. Both our functional and genetic studies support R43H as the cause of GCK-MODY and G68D as a neutral rare variant. CONCLUSIONS: These data highlight the need for family/functional studies, even for previously reported pathogenic mutations.